Orotate phosphoribosyltransferase is overexpressed in malignant pleural mesothelioma: Dramatically responds one case in high OPRT expression. Issue 1 (1st January 2016) - Hamamoto, Yoichiro; Takeoka, Shinjiro; Mouri, Atsuto; Fukusumi, Munehisa; Wakuda, Kazushige; Ibe, Tatsuya; Honma, Chie; Arimoto, Yoshihito; Yamada, Kazuaki; Wagatsuma, Miyuki; Tashiro, Akito; Kamoshida, Shingo; et al.
ABSTRACT: Objective: Malignant pleural mesothelioma (MPM) is a rare and aggressive, treatment-resistant cancer. Pemetrexed, an inhibitor of thymidylate synthase (TS), is used worldwide for MPM as a first-line chemotherapy regimen. However, there is little consensus for a second-line chemotherapy. S-1, a highly effective dihydropyrimidine dehydrogenase (DPD)-inhibitory fluoropyrimidine, mainly acts via a TS inhibitory mechanism similar to pemetrexed. Orotate phosphoribosyltransferase (OPRT) is a key enzyme related to the first step activation of 5-fluorouracil (5-FU) for inhibiting RNA synthesis. We investigated 5-FU related-metabolism proteins, especially focusing on OPRT expression, in MPM Methods and Patients: Fifteen MPM patients who were diagnosed between July 2004 and December 2013 were enrolled. We examined the protein levels of 5-FU metabolism-related enzymes (TS, DPD, OPRT, and thymidine phosphorylase [TP]) in 14 cases Results: High TS, DPD, OPRT, and TP expressions were seen in 28.6%, 71.4%, 85.7%, and 35.7% of patients, respectively. We found that OPRT expression was extremely high in MPM tissue. We experienced one remarkable case of highly effective S-1 combined therapy for pemetrexed refractory MPM. This case also showed high OPRT protein expression Conclusion: The present study suggests that OPRT expression is high in MPM tumors. Although pemetrexed is mainly used for MPM chemotherapy as a TS inhibitor, S-1 has potential as an anticancer drug not only as a TS inhibitor but also inhibiting RNA synthesis through the OPRT pathway. This is the first report investigating OPRT protein expressions in MPM.